2022
DOI: 10.1111/cid.13150
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of retention of the buccal root section combined with immediate implant placement: A systematic review of longitudinal studies

Abstract: Introduction: Immediate implant placement in conjunction with partial extraction therapy has been shown to result in functional osseo-and dento-integration with partial preservation of the periodontal ligament (PDL) in humans. Strategic buccal root retention for PDL preservation is a biologically driven procedure that maintains alveolar ridge dimensions and esthetics, while allowing for implant placement. The aim of this study was to conduct a systematic review of longitudinal clinical outcomes of PDL-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…17 Previous clinical studies have consistently reported superior periimplant bone maintenance and higher PES in cases of immediate single implant placement utilizing the socket shield (SS) technique compared to conventionally inserted implants. [18][19][20][21][22][23] The SS technique involves the retention of the facial root fragment during extraction and removal of the palatal portion of the root and apex. Subsequently, the implant is placed lingual to the retained root fragment during the same or subsequent session.…”
Section: Introductionmentioning
confidence: 99%
“…17 Previous clinical studies have consistently reported superior periimplant bone maintenance and higher PES in cases of immediate single implant placement utilizing the socket shield (SS) technique compared to conventionally inserted implants. [18][19][20][21][22][23] The SS technique involves the retention of the facial root fragment during extraction and removal of the palatal portion of the root and apex. Subsequently, the implant is placed lingual to the retained root fragment during the same or subsequent session.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Importantly, a recent clinical study provided evidence that the root-membrane (RM) technique for PDL-mediated implant placement is non-inferior to no extraction based on volumetric and radiographic data 21 , whereas a recent systematic review of longitudinal studies concluded that strategic retention of the buccal root has a benefit in terms of dimensional ridge stability over conventional immediate implantation when implemented in carefully selected cases. 22 Collectively, this emerging body of evidence is on the verge of supporting PDL-mediated implant placement techniques as mainstream treatment modalities. Nonetheless, because of the recency of these techniques, little is known about the possible complications arising from their application and their management.…”
Section: Introductionmentioning
confidence: 99%